SLEEP DISTURBANCE AND QUALITY OF SLEEP AMONG PATIENTS WITH CARDIOVASCULAR DISEASES - Merin, Neenu; Antony, Regina (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This was a descriptive study with the objective to determine the sleep disturbances and the quality of sleep among patients with cardiovascular diseases (CVDs). Methods: Quantitative approach with non-experimental descriptive design was used. A semi-structured sleep disturbance questionnaire was used to determine the sleep disturbances, and a standardized Pittsburgh Sleep Quality Index tool was used to assess the sleep quality among 100 subjects in Amrita Institute of Medical Sciences, Kochi. Results: The study results showed that majority of the subjects (51%) were of the age group between 56 and 65 years, and 71% were male with CVD. Sleep disturbances were present in 80% of the subjects with CVD, among which 56% subjects had mild disturbances, 20% subjects with moderate sleep disturbances, and 4% subjects with severe sleep disturbances. The result also indicated that 48% of subjects had poor sleep quality. Findings also showed a highly statistically significant association between cardiomyopathy and sleep disturbances (p<0.001). Total cholesterol and low-density cholesterol levels were significantly associated with sleep disturbances (p<0.05). There is a highly significant association between sleep disturbances and quality of sleep (p<0.001), indicating that sleep disturbances can be one factor in decreasing the quality of sleep in patients with CVD. Conclusion: The results of the study indicated that sleep disturbances were prevalent in patients with CVD and often hazardous to heart health. As health practitioner and other health-care providers have not focused major attention on the importance of sleep to health, the need for providing information to them and patients regarding the importance of improving the quality of sleep and identifying the sleep disturbances will call for action to bring sleep to the forefront of public health.